Capital Markets and Financial Intermediation in The Baltics - Sheridan, Niamh (Occasional Papers; Occasional Paper ;, 2004)
In just over a decade after independence, the three Baltic countries, Estonia, Latvia, and Lithuania, have transformed themselves into fully functioning, small open-market economies that will be joining the European Union. Capital Markets and Financial Intermediation in The Baltics analyzes the financial systems of the three countries and discusses some of their unique characteristics. The study also examines current distortions of the systems and discusses whether or not the Baltics should move from an almost exclusively bank-based system to one that relies more on capital markets. In the process, it addresses issues of corporate governance and regional integration.